Solving the Problem of Forensic Identification of a Person’s Appearance Based on Video Materials: An Integrated Approach (Law, State and Telecommunications Review, 2023)
[Purpose] The purpose of this study is a comprehensive investigation of modern techniques and developments for recording and analyzing data about the criminal.[Methodology/Approach/Design] Theoretical and empirical methods, such as statistical analysis, synthesis, induction and deduction, were used for the study. The practical scope of this article includes research by Chinese, Ukrainian, Russian and English researchers in this field. Scientists studied the theoretical and practical scientific literature on the topic, as well as the achievements of modern science in the field of improving video surveillance systems, in order to analyze.[Findings] It was found that in the context of digitalization, law enforcement agencies can gain access to personal biometric data of citizens, which, on the one hand, simplifies the search for an alleged criminal, and on the other hand, intrudes into the privacy of citizens, thereby violating the law. However, modern security systems and artificial intelligence built into surveillance cameras undoubtedly help solve crimes.[Practical Implications] The applied value of this study lies in the identification of current issues of both Ukrainian criminal legislation and legislation related to the protection of personal data and their use by law enforcement agencies of such states as the People’s Republic of China, the United States of America, the United Kingdom, the Russian Federation.